Consensus on Exercise Reporting Template (CERT): Explanation and Elaboration Statement. Issue 23 (5th October 2016) - Slade, Susan C; Dionne, Clermont E; Underwood, Martin; Buchbinder, Rachelle
Abstract : Exercise is effective for prevention and management of acute and chronic health conditions. However, trial descriptions of exercise interventions are often suboptimal, leaving readers unclear about the content of effective programmes. To address this, the 16-item internationally endorsed Consensus on Exercise Reporting Template (CERT) was developed. The aim is to present the final template and provide an Explanation and Elaboration Statement to operationalise the CERT. Development of the CERT was based on the EQUATOR Network methodological framework for developing reporting guidelines. We used a modified Delphi technique to gain consensus of international exercise experts and conducted 3 sequential rounds of anonymous online questionnaires and a Delphi workshop. The 16-item CERT is the minimum data set considered necessary to report exercise interventions. The contents may be included in online supplementary material, published as a protocol or located on websites and other electronic repositories. The Explanation and Elaboration Statement is intended to enhance the use, understanding and dissemination of the CERT and presents the meaning and rationale for each item, together with examples of good reporting. The CERT is designed specifically for the reporting of exercise programmes across all evaluative study designs for exercise research. The CERT can be used by authors to structure intervention reports, by reviewers and editors to assess completeness of exercise descriptions and by readers to facilitate the use of the published information. The CERT has the potential to increase clinical uptake of effective exercise programmes, enable research replication, reduce research waste and improve patient outcomes.